Urgensi Manajemen Bimbingan dan Konseling dalam Melahirkan Peserta Didik Berkarakter - Shella Satiwi Guci; Neviyarni; Firman (Education & Learning, 2022)
The success of education in schools is largely determined by the expertise and managerial abilities of the principal. No exception managing the ability of educators and education in schools will be directly proportional to the success of schools in carrying out their programs. In this context, guidance and counseling management (BK) is important to be developed to give birth to students with noble character or character. Character education is strongly influenced by a character environment as well. Therefore, the creation of a conducive environment with the application of appropriate guidance and counseling management will have a significant effect on improving the quality of students in absorbing moral values both inside and outside the school. Character education that must be developed in schools knows no time limit because it is a lifelong process. In addition to schools, the existence of families and communities is also important in the process of internalizing character formation.